RUSSIA: POLITICAL MOBILIZATION OF APOLITICAL SOCIETY - Кремень, Т.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
The article is dedicated to social media mobilization in post-Soviet space in context of consistent apathy of Russian society. It is concluded that social media play a crucial role in political participation encouragement of oppositional public.  Nevertheless the transient effect of socio-media mobilization is specified which was followed by the protest capacity decline.